Study of the subsolidus structure of the system ZnO–Al2O3–TiO2–SiO2 - Pitak, Yaroslav; Lisachuk, Georgy; Podchasova, Katerina; Bilostotska, Lubov; Trusova, Yulia; Krivibok, Ruslan (Eastern-European Journal of Enterprise Technologies, 2016)
The study of the structure of the system ZnO–Al2O3–TiO2–SiO2 in the field of subsolidus using thermodynamic and geometric-topological methods, as well as the structure of poorly explored three-component systems ZnO – Al2O3 – TiO2 and ZnO – TiO2 – SiO2, is conducted. It is found that the four-component system is divided into eight elementary tetrahedra. Their relative volumes, the degree of asymmetry are calculated. The lengths of tie lines, the relative volumes of phase existence, and probability of phase coexistence are determined. The topological graph of the relationship of the elementary tetrahedra is built. The geometric-topological characteristics of the system phases (volume of existence, probability of coexistence) are provided. The regions of oxide compositions with the largest relative volumes and the lowest degree of asymmetry for manufacturing a wide range of refractories, heat-resistant and technical ceramics, and also glass-crystalline materials and coatings are shown. The region of oxide compositions with a minimum temperature (1170 K) of melt occurrence, which is promising for producing materials under forced firing is determined. These data, in addition to identifying common statistical regularities, can be the basis for the synthesis of the given phase composition with the desired set of properties and implementation of energy-saving technologies.